Implementation of Hotelling’s T2 Method in Quality and Capability Control of Newlab Collagen Production Processes - Indrani , Rahmadana Kadija; Kariyam, Kariyam (Enthusiastic : International Journal of Applied Statistics and Data Science, 2025)
Every company has quality standards that are determined for the production process. However, there are factors that occur in the production process that causes defects in the product. From these problems, this research was conducted to analyze the quality control, causal factors, and performance of the production process on Newlab Collagen products. The methods used in production quality control were Hotelling’s T2 control chart, fishbone diagram, and process capability analysis. In the Hotelling’s T2 control chart, the multivariate observation data was divided into two phases, with five quality indicators. The results of the first phase of the Hotelling’s T2 control map showed that the quality indicators of the Newlab Collagen production were out of control, which caused by unstable machine factors. Based on control chart, the second phase showed that the quality indicators of the Newlab Collagen production process were still out of control. This condition was evidenced by the process capability value in phase I and phase II being less than one. These findings suggest that the company needs to make improvements, optimization, and quality control in the production.